2021
DOI: 10.3389/fpubh.2021.680967
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction Model for Esophageal Cancer Among General Population: A Systematic Review

Abstract: Objective: The risk prediction model is an effective tool for risk stratification and is expected to play an important role in the early detection and prevention of esophageal cancer. This study sought to summarize the available evidence of esophageal cancer risk predictions models and provide references for their development, validation, and application.Methods: We searched PubMed, EMBASE, and Cochrane Library databases for original articles published in English up to October 22, 2021. Studies that developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Former smokers surviving a lung or head and neck cancer should be surveilled endoscopically for a second primary ESCC [16]. Risk prediction models for esophageal cancer among the general population and biomarkers for early detection are being evaluated [18, 19].…”
Section: Esophageal Squamous Cell Cancermentioning
confidence: 99%
“…Former smokers surviving a lung or head and neck cancer should be surveilled endoscopically for a second primary ESCC [16]. Risk prediction models for esophageal cancer among the general population and biomarkers for early detection are being evaluated [18, 19].…”
Section: Esophageal Squamous Cell Cancermentioning
confidence: 99%
“… 11 Existing prediction models (eTable 1 in Supplement 1 ) were limited and have many defects. 16 , 18 , 19 Prediction models based on case-control studies have low evidence quality, 20 , 21 , 22 , 23 and cohort-based models rarely perform external validation, tend to be based on questionnaire data, and do not consider endoscopic-related risk factors. 24 , 25 Therefore, this report aims to establish and validate ESCC prediction models for the follow-up stage of esophageal cancer screening and to optimize the esophageal cancer screening program.…”
Section: Introductionmentioning
confidence: 99%
“…The development direction of esophageal cancer screening is precision, individualization, and risk prediction based; therefore, the prediction model plays an important role . Existing prediction models (eTable 1 in Supplement 1) were limited and have many defects . Prediction models based on case-control studies have low evidence quality, and cohort-based models rarely perform external validation, tend to be based on questionnaire data, and do not consider endoscopic-related risk factors .…”
Section: Introductionmentioning
confidence: 99%
“…More than 300,000 people are diagnosed with esophageal cancer (ESCA) every year, making it one of the most common malignant tumors of the upper gastrointestinal tract and a serious threat to human health [ 1 , 2 ]. Recent researches have indicated that a combination of factors, such as unhealthy lifestyle choices, exposure to carcinogens, underlying disorders, and genetics, has a role in the development of esophageal cancer [ 3 , 4 ]. There are a number of risk factors that can enhance an individual's susceptibility to ESCA.…”
Section: Introductionmentioning
confidence: 99%